RANCANG BANGUN RUBU’ MUJAYYAB SEBAGAI INSTRUMEN FALAK KLASIK - Akhmad Nadirin, Akhmad Nadirin; Setyawan, Edy; Wiguna, Akhmad Faiz; Nahwandi, M. Syaoqi (ELFALAKY: Jurnal Ilmu Falak, 2023)
Astronomical Instruments or Astronomy is a scientific icon that is clear evidence of the development of Astronomy in classical Western and Islamic civilization. Even though the classical Falak instrument is simple, it holds extraordinary scientific treasures. Rubu' Mujayyab is an instrument used by humans to observe and calculate the positions of celestial bodies before telescopes and logarithm tables were invented. In the current era of technological development, Classical Falak Instruments such as the Rubu' Mujayyab need to be developed and adapted to technological advances into software or digital applications in order to continue to exist. This research aims to design the Javascript-based Rubu' Mujayyab application and determine the results of functionality testing and evaluation of the Javascript-based Rubu' Mujayyab digital application. This research was conducted using the Research and Development method. In this research, the classical astronomical instrument was digitally developed using the JavaScript programming language. The Falak instrument developed is Rubu' Mujayyab. This instrument is a classic astronomical instrument which is still relevant to current conditions and is widely used in studying astronomy in Madrasas, Islamic boarding schools and Islamic universities. After the digital application of the classic astronomical instrument was created, it was then validated with an instrument validation sheet by an Expert Researcher from Imah Noong, Lembang, namely Hendro Setyanto, as well as testing the functionality of the two applications. The result is a classic digital falak application, namely rubu' al-mujayyab itself. Apart from that, based on the results of functionality tests by Expert Researchers, it was found that this digital application can run and function well according to the function of the physical instrument.